Pengaruh Kapabilitas, Visibilitas, Terhadap Performa Rantai Pasokan dan Perusahaan yang Dimoderasi Jumlah Karyawan, Usia Perusahaan - Wisely Taswin, Ladyta; Fajar Arianto, Radityo (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to analyze the impact of capabilities, visibility, and supply chain resilience on supply chain performance and company performance, with the moderating variables of the number of employees and company age. The subjects of this study are directors, managers, supervisors, or staff/operators from various industrial companies in Indonesia. The research sample consists of 140 respondents, selected using a non-probability sampling technique with purposive sampling. Data collection was conducted using questionnaires distributed via Google Forms and measured with a five-point Likert scale. For data processing, this study employs Structural Equation Model (SEM) Partial Least Square (PLS) analysis using the SMART-PLS version 3 software. The results of this study are as follows: supply chain capabilities and visibility have a significant impact on supply chain resilience, supply chain performance, and company performance, with supply chain resilience serving as a mediating variable. Additionally, supply chain performance significantly affects company performance. Company age does not moderate the relationship between capabilities and supply chain resilience. Similarly, the number of employees does not moderate the impact of supply chain capabilities on supply chain resilience